Prescribed medications for patients with amphetamine-type stimulant use disorder seen in rural-serving Pacific Northwest primary care clinics - Megan J. Yerton; Connor J. McCabe; Matthew D. Iles-Shih; Judith I. Tsui; Kevin A. Hallgren (Addiction Science & Clinical Practice)
Abstract Background Amphetamine-type stimulant use and overdoses have increased sharply across the US in recent years, largely driven by methamphetamine. Increased access to treatments for amphetamine-type stimulant use disorder (AT-StUD), including in primary care settings, is needed to mitigate these problems, yet effective behavioral treatments are often inaccessible and there are no FDA-approved medications for AT-StUD. In the current study, we characterize how often patients with clinically documented AT-StUD in predominantly rural-serving Pacific Northwest primary care clinics received medications that have been conditionally recommended in practice guidelines for treatment of AT-StUD. Methods Electronic health record data from 23 primary care clinics in the Pacific Northwest US were obtained through the Data QUEST network. Adult patients with clinically documented “other stimulant abuse” or “other stimulant dependence” diagnoses typically reflecting AT-StUD between 01/2017 and 12/2021 were included. Prescription records were used to identify orders for bupropion, mirtazapine, topiramate, naltrexone-bupropion combination, methylphenidate, dextroamphetamine, and modafinil. Statistical analyses quantified the percentage of patients with medication orders placed within one year after any documented AT-StUD diagnosis. Results Patients (N = 963) were predominantly female (53.3%), White (81.7%), and non-Hispanic (70.5%). In total, 14.3% of patients received orders for a non-stimulant medication conditionally recommended in practice guidelines; 2.7% received orders for a stimulant medication. Consistent with clinical guidelines, medications were more often prescribed when patients had documented co-occurring disorders for which the medications could also be effective. Conclusions In this sample of rural-serving primary care clinics, approximately 1 in 7 primary care patients with AT-StUD received orders for medications with preliminary evidence of effectiveness. Efforts are needed to increase access to AT-StUD treatments within primary care. These efforts could include training health professionals to consider judicious use of pharmacotherapy consistent with clinical guidelines, increasing capacity for behavioral health services including contingency management, and continuing research on pharmacologic agents.